Reforms, Organizational Change and Performance in Higher Education
XX, 326 p. 26 illus., 1 illus. in color.
Keywords: This open access book investigates the effects of changes in leadership and managerial structures of Nordic universities resulting from reforms in the last decade. It builds on a rich, comparative dataset across a multiplicity of system-wide (macro) and organisational (meso and micro) dimensions, namely: reform or policy initiatives; drivers, aims, instruments and actors; structural changes within universities; strategic and performance management; the rise of accountability regimes; incentive and evaluative systems; and perceived changes/effects by the key actors involved, at various levels. The volume provides critical insights to the larger phenomenon of change and adaptation within the public sector. Its findings and implications are of relevance to social science researchers, policy makers, managers/administrators, and external stakeholders. Rómulo Pinheiro is Professor of Public Policy and Administration at the Department of Political Science and Management at the University of Agder, Norway. Hanne Foss Hansen is Professor in Public Organisation and Administration at the Department of Political Science, University of Copenhagen, Denmark. Lars Geschwind is Associate Professor in Engineering Education Policy and Management at the Department of Learning, KTH Royal Institute of Technology, Stockholm, Sweden. Kirsi Pulkkinen is a researcher at the Faculty of Social Sciences at the University of Lapland, Finland, and Advisor of co-creation at the Research Services of University of Helsinki, Finland.